2022
DOI: 10.3390/cancers14071845
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Hyperpolarized [1-13C]Pyruvate in Breast Cancer Cells Depends on Their Malignancy, Metabolic Program and Nutrient Microenvironment

Abstract: Hyperpolarized magnetic resonance spectroscopy (MRS) is a technology for characterizing tumors in vivo based on their metabolic activities. The conversion rates (kpl) of hyperpolarized [1-13C]pyruvate to [1-13C]lactate depend on monocarboxylate transporters (MCT) and lactate dehydrogenase (LDH); these are also indicators of tumor malignancy. An unresolved issue is how glucose and glutamine availability in the tumor microenvironment affects metabolic characteristics of the cancer and how this relates to kpl-val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 72 publications
1
7
0
Order By: Relevance
“…In this paper, a lack of correlation of malignancy with LDH activities was reported. This is corroborated by studies with breast cancer xenografts in vivo [51] and cell lines in vitro [52]. Such a lack of correlation between pyruvate-to-lactate conversion and malignancy was also reported for hepatocellular carcinoma [53].…”
Section: Breast Cancersupporting
confidence: 63%
“…In this paper, a lack of correlation of malignancy with LDH activities was reported. This is corroborated by studies with breast cancer xenografts in vivo [51] and cell lines in vitro [52]. Such a lack of correlation between pyruvate-to-lactate conversion and malignancy was also reported for hepatocellular carcinoma [53].…”
Section: Breast Cancersupporting
confidence: 63%
“…The mitochondria is also regarded as the powerhouse of the cell because its function is to synthesize energy molecules in the form of ATP [ 33 ]. The mitochondria also plays a significant role in metabolic pathways such as beta-oxidation, pyruvate decarboxylation, ketogenesis, and apoptosis initiation accomplished via ROS generation and apoptotic proteins activation [ 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Exometabolomics further revealed that MDA-MB-231 cells, especially when cultured in hypoxia, and all macrophage subsets (M0 and TEM included) excrete citrate. Citrate secretion is a well-known feature of prostate epithelial cells [44] and astrocytes [45], where it is associated with specific physiological functions, but has seldom been reported for other cell types. Our observation that MDA-MB-231 cells, but not MCF-7 cells, secrete citrate may relate to the very recent findings by Grashei et al showing increased pyruvate influx into the TCA cycle in MDA-MB-231 cells compared to MCF-7 cells [45].…”
Section: Discussionmentioning
confidence: 99%
“…Citrate secretion is a well-known feature of prostate epithelial cells [44] and astrocytes [45], where it is associated with specific physiological functions, but has seldom been reported for other cell types. Our observation that MDA-MB-231 cells, but not MCF-7 cells, secrete citrate may relate to the very recent findings by Grashei et al showing increased pyruvate influx into the TCA cycle in MDA-MB-231 cells compared to MCF-7 cells [45]. Further, in that study, pyruvate-derived citrate was shown to partially originate from pyruvate carboxylation to oxaloacetate and reverse TCA cycle, which is in line with the high pyruvate carboxylase (PC) activity in BC tissues and MDA-MB-231 cells [46,47].…”
Section: Discussionmentioning
confidence: 99%